Determinan Adopsi Sistem Tanam Benih Langsung (Tabela) dalam Pengkajian Sutpa (Kasus SUTPA di Propinsi Jawa Timur dan Lampung) - Rachmat Hendayana; Handewi P. Saliem (Jurnal Agro Ekonomi, 1997)
The research was undertaken on Direct Seeded Rice technology (Tabela) performance, particularly to test relevant factors affecting adoption of direct seeded rice. It was conducted in Lampung and East Java. The analysis of 120 agribusiness oriented rice based farming system (SUTPA) cooperator farmers was conducted by using logit model. The result shows that technology have the comparative advantage than transplanting metode in rice cultivation. Adoption of direct seeded rice influenced significantly by land ownership, cost of planting and maintenance, planting season, researcher or extention worker guidance and location. Based on the result, the Tabela technology is suitable to be developed in the region where there is a shortage of agricultural labor occure. It reduces labor and cost for planting and maintenanace which increase income of the farmers. However, the sosialization of direct seeded rice technology is still needed guidance from researcher and extension workers.